Investigating the composition of the K0⁎(700) state with π±KS0 correlations at the LHC - Acharya, S.; Adamovã, D.; Aglieri Rinella, G.; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; et al. (Elsevier, 2024)
The first measurements of femtoscopic correlations with the particle pair combinations 𝜋±K0 S in pp collisions at √𝑠 = 13 TeV at the Large Hadron Collider (LHC) are reported by the ALICE experiment. Using the femtoscopic approach, it is shown that it is possible to study the elusive K∗ 0(700) particle that has been considered a tetraquark candidate for over forty years. Source and final-state interaction parameters are extracted by fitting a model assuming a Gaussian source to the experimentally measured two-particle correlation functions. The final-state interaction in the 𝜋±K0 S system is modeled through a resonant scattering amplitude, defined in terms of a mass and a coupling parameter, The extracted mass and Breit–Wigner width, derived from the coupling parameter, of the final-state interaction are found to be consistent with previous measurements of the K∗ 0(700). The small value and increase of the correlation strength with increasing source size support the hypothesis that the K∗ 0(700) is a four-quark state, i.e. a tetraquark state of the form (q1, q2, q3, q3) in which q1, q2 and q3 indicate the flavor of the valence quarks of the 𝜋 and K0 S. This latter trend is also confirmed via a simple geometric model that assumes a tetraquark structure of the K∗ 0(700) resonance.
Keywords: Physics; Tetraquark; Particle physics; Valence (chemistry); Quark; Hadron; Nuclear physics; Quantum mechanics; https://purl.org/pe-repo/ocde/ford#1.03.04